-6=3x-48

Simple and best practice solution for -6=3x-48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=3x-48 equation:


Simplifying
-6 = 3x + -48

Reorder the terms:
-6 = -48 + 3x

Solving
-6 = -48 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-6 + -3x = -48 + 3x + -3x

Combine like terms: 3x + -3x = 0
-6 + -3x = -48 + 0
-6 + -3x = -48

Add '6' to each side of the equation.
-6 + 6 + -3x = -48 + 6

Combine like terms: -6 + 6 = 0
0 + -3x = -48 + 6
-3x = -48 + 6

Combine like terms: -48 + 6 = -42
-3x = -42

Divide each side by '-3'.
x = 14

Simplifying
x = 14

See similar equations:

| 5i+(-9-i)= | | 11/4x=3/4+x | | cos(6x)+cos(4x)=0 | | 10-x/2=x+4/5 | | 5(2a-3)-9a=-8 | | 3v-5/4=-7/2v+5/3 | | y=-3.9x^2+19.5x | | w/4+5=m/3+10 | | P=18x+10y | | x^3/4 | | .20y-1.8=.10y+1-0.6y | | -84/7 | | 2x-7x+23=12 | | w/4+5=m/3-10 | | w/4+17=m/2-7 | | 2x+170=9x-12 | | 1/6+x=3/4x+1/3 | | 2(6+1)-4= | | x^6=16x^3 | | 4x+7=-5x+5 | | 4x+7=-5+5 | | 9x^2+5x-25=0 | | (2-3i)+(4+8i)= | | 4/12=s/16 | | B/16=a | | 0.5n-2=3 | | 3y-1=1 | | (-6+i)(-6-1)= | | 3x+12=24-9x | | 2x-5/7+x+3/2 | | x^2+12x-324=0 | | 6x(25-15)+8= |

Equations solver categories